Achados em citologia de impressão de conjuntiva exposta ao Interferon a2b e à mitomicina C 0,02%: estudo experimental em coelhos - Almeida, Simone Ribeiro Araujo de [UNIFESP] (2016)
Objective: To describe impression cytology findings from samples taken from rabbit?s healthy conjunctiva that received INFa2b drops and to compare it to the findings observed after the use of MMC 0,02%. Methods: An experimental study on animal model was done between September 2013 and October 2014. This study was done in Faculdade de Medicina de Marília, Unifesp and Clínica de olhos Moacir Cunha. Thirty New Zealand albino rabbits were divided into 6 groups and received INFa2b or MMC 0,02%. Impression cytology (CI) was performed before the use of drugs and after 15, 30 and 60 days since the drops began. For the CI analysis we consider goblet cells, cellularity, intercellular adhesion, nucleus/cytoplasm (NC) ratio, chromatin, inflammatory cells, keratinization and cytomegaly. Results: The main findings in CI after the use of INFa2b drops were reduction in goblet cells (50,8%) and in intercellular adhesion (26,2%), change on NC ratio (20%) and cellularity reduction. After the use of MMC 0,02% the most common alterations were reduction in goblet cells (46,2%), change on NC ratio (25,6%) and reduction of intercellular adhesion (23,1%) and cellularity (20,5%). There was no statistical significant difference for any variables analyzed when compared the CI findings after INFa2b to the findings after MMC 0,02%. For both drugs, goblet cells showed more reduction on CI taken on day 30 and 60 when compered to the CI taken on day 15. Conclusion: the reduction of goblet cells, intercellular adhesion and cellularity and the change on NC ratio were the most common findings on CI token from healthy rabbit?s conjunctiva after the use of INFa2b drops. These findings were similar to the ones seen on CI after MMC 0,02%. Future study is necessary to see whether these findings happen on the CI taken from human conjunctiva or not.